Microextração em fase líquida no preparo de amostra de plasma para análise cromatográfica de fluoxetina e norfluoxetina - Freitas, Daniela Fernanda De (2009)
Antidepressants, such as fluoxetine (FLU) and its active metabolite norfluoxetine (NORFLU), are drugs for which the analysis in biological fluids is of high interest in various areas of application. New trends in the miniaturization of sample pretreatment techniques have been identified in order to use methods that consume less quantity of organic solvents, among them, liquid-phase microextraction (LPME). Therefore, the aim of this work was to develop and validate an analytical method using high performance liquid chromatography coupled to LPME for the analysis of fluoxetine and norfluoxetine in plasma samples. The use of a reverse phase Select B column (125 mm x 4 mm x 5 μm) 0.005 mol L-¹ sodium acetate buffer, pH 4.5: acetonitrile (50:50, v/v) as mobile phase at flow rate of 0.6 mL min-¹, and a fluorescence detector at wavelengths of excitation at 230 nm and emission at 290 nm, resulted in satisfactory chromatographic resolution and efficiency for the analytes. Three-phase LPME system using a disposable 7-cm polypropylene porous hollow fiber, 1 mL of plasma, n-hexyl ether (extractor solution) and 20 mmol L-¹ hydrochloric acid (acceptor solution) were used in the extraction. After optimization of several parameters influencing LPME efficiency (organic extraction solvent, extraction time, stirring speed, type and pH of acceptor solution, pH of sample solution, use of salt and organic solvent in the donor phase) the method was validated. Linearity over a 5 – 500 ng mL-¹ range with determination coefficients (R2) of 0.9999 and 0.9962, respectively for FLU and NORFLU were established. Extraction recovery from plasma samples were 70.9 % for FLU and 59.7 % for NORFLU. The intra-assay and inter-assay precision and accuracy were studied for three concentrations (20, 80 and 160 ng mL-¹) and for both analytes the coefficients of variation were less than 13.0 % with acceptable accuracy. The LPME extraction followed by HPLC-fluorescence detection for FLU and NORFLU analysis, using venlafaxine as internal standard, showed excellent sample clean-up as well as high selectivity, being simple, inexpensive, and ease to perform, with a satisfactory enrichment of the drugs. The method was successfully applied to the analysis of samples from twelve patients under fluoxetine treatment and proved to be suitable in routine therapeutic drug monitoring of the antidepressants.